The transcription factor ZmNAC84 increases maize salt tolerance by regulating ZmCAT1 expression - Yitian Pan; Tong Han; Yang Xiang; Caifen Wang; Aying Zhang (Crop Journal)
Salt stress severely affects plant growth and yield. The transcription factor NAC plays a variety of important roles in plant abiotic stress, but we know relatively little about the specific molecular mechanisms of NAC in antioxidant defense. Here, our genetic studies reveal the positive regulation of salt tolerance in maize by the transcription factor ZmNAC84. Under salt stress, overexpression of ZmNAC84 in maize increased the expression of ZmCAT1, enhanced CAT activity, and consequently reduced H2O2 accumulation, thereby improving salt stress tolerance in maize. Whereas RNA interference-mediated knockdown of ZmNAC84 produced the opposite effect. Subsequently, we found that ZmNAC84 directly binds to and regulates the expression of the ZmCAT1 promoter, and the hybridized material also demonstrated that ZmCAT1 is a downstream target gene of ZmNAC84. In addition, phenotypic and biochemical analyses indicated that ZmCAT1 positively regulated salt tolerance by regulating H2O2 accumulation under salt stress. Taken together, these results reveal the function of ZmNAC84 in regulating ZmCAT1-mediated antioxidant defense in response to salt stress in plants.